Sistemas numéricos e Ensino de Ciências: construção do conhecimento matemático de povos indígenas do Alto Rio Negro - Freitas, Rejane Maria Caldas (2011)
This work entitled "Numeric Systems and Teaching of Sciences: construction of the mathematical knowledge of indigenous people of high Rio Negro" presents bibliographies analyses relating the systems of numbering of culturally different people and to the process teaching-learning of the Mathematics in the indigenous and noindigenous schools. The indigenous numeric systems are several as they are diversified races. The analyzed people present numeric systems with base two, base five, base ten and base twenty. However, the investigation points out that the theoretical ones are limited to the linguistic studies, disrespecting the conceptions and the mathematical beginnings that are applied in the practices of the daily and in the productions of instruments and workmanships. For the development of that work, we used the hermeneutic as methodology and the technique of content analysis. The theoretical reference took for base ethnographic researches, accomplished by missionaries, anthropologists, linguists and indigenous, showing that, due to the contact with other societies, the natives suffered strong cultural influence. We detected the change in the behavior, in the daily activity and, mainly, in the language. It is perceptible that the alteration in the original language hinders the collection of information on the systems of numbering of the races. However, the accomplished study had the focus in a perspective of intercultural education with the intention of showing that the indigenous people have own ways to know/do, of learning and of teaching mathematics. This way, the elaborated product makes possible the intercultural relationship, through the teaching of the numeric systems in the 6th year of the middle school in the indigenous and no-indigenous schools. We believe that the work in its totality contributes to the spread of an intercultural education and that the Mathematics to be seen as the union of several mathematics of different people.